Kemampuan Memilih Saham dan Market Timing Manajer Investasi Reksa Dana Saham di Bursa Efek Indonesia - Waelan Waelan (Jurnal Akuntansi dan Auditing Indonesia, 2008)
Purpose of this article is to analyze equity mutual fund investment manager ability in Indonesian Stock Exchange by applying quadratic timing factor. The result indicate that investment manager of equity mutual fund in Indonesian Stock Exchange have no security selection ability and have small positive market timing ability. At the individual fund level, there are 4 investment manager have security selection ability, 3 investment manager have market timing ability, and 1 investment manager have both. There are trade-off between security selection ability and market timing ability. Keywords: Equity mutual fund, security selection ability, market timing ability, and trade-off.